ANALYSIS OF GRAMMATICAL COHESION AND LEXICAL COHESION IN THE NOVEL KATRESNAN BY SOERATMAN SASTRADIHARDJA - Istifani, Duwik; Rochimansyah, Rochimansyah; Setyowati, Herlina (Department Javanese Literature and Language Education in Collaboration with Faculty of Teacher Training and Education Muhammadiyah University of Purworejo, 2024)
This research aims to describe markers of grammatical cohesion contained in the novel Katresnan by Soeratman Sastradihardja, and markers of lexical cohesion contained in the novel Katresnan by Soeratman Sastradihardja. This type of research is qualitative descriptive research. The source of research data is the novel Katresnan by Soeratman Sastradihardjo. The data for this research are sentences containing grammatical cohesion and lexical cohesion in the novel Katresnan by Soeratman Sastrodihardja. Data collection techniques use listening techniques and note-taking techniques. The research instrument is the researcher himself as the main instrument, assisted by discourse books, books that support research and data recording notes. The data analysis technique uses content analysis techniques. The data analysis presentation technique uses informal presentation techniques. The results of the research are: forms of grammatical aspect cohesion markers include: references consisting of referring to person I, referring to person II, referring to person III; Demonstrative reference consists of time and place demonstratives; comparative referencing; substitution (replacement); ellipsis (dissolution) and conjunction (series) consisting of causal conjunctions, conflicting conjunctions, exception conjunctions, concessive conjunctions, additional conjunctions, choice conjunctions, expectation conjunctions, sequence conjunctions, time conjunctions, and conditional conjunctions. The forms of lexical aspect markers include; The repetitions found were epizeuksis repetition, tautotes repetition, anaphora repetition, epistrophe repetition, mesodiplosis repetition, synonyms (similar words), antonyms (opposite words), collocations (opposite words) and equivalence.